Eksistensi Pengadilan Tata Usaha Negara Dalam Sistem Ketatanegaraan Republik Indonesia: Keadilan, Peradilan Tata Usaha Negara, Sistem Tata Negara - Abi Sugara; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2022)
The State of Indonesia is one of the legal countries where this makes all aspects of life, whether it's actions, behavior, even daily behavior is always related to the law in the eyes of the law, all are proper and equal, there is nothing special, whether it is ordinary people or officials, all are the same in the eyes of the law. which legal eye in making Indonesia need an institution that can enforce law and justice in Indonesia and that institution is the PTUN or what we call the state administrative court, PTUN is one of the judicial institutions under the auspices of the supreme court, as one of the One of the institutions that are trusted by the state to enforce law and justice, the Administrative Court is an institution that has the right to exercise judicial power in the state of Indonesia considering that Indonesia is a state of law as described in the 1945 Constitution, therefore this paper aims to find out the role and function of the Administrative Court as one of the Enforcement agency law and justice in Indonesia.